Assessing knowledge gaps of para extension workers for improving their capacity in dissemination of farm technology to farmers in Mandi district of Himachal Pradesh, India - CHAHAL, V P; YADAV, D S; THAKUR, S K; SOOD, PANKAJ (The Indian Journal of Agricultural Sciences, 2015)
Public extension systems worldwide including India are facing serious challenges in dissemination of technolog due to shortage of technical manpower. The services of trained Para Extension Workers (PEWs) could be used provided they have good knowledge of modern farming methods. Therefore, knowledge gaps assessment is crucial for designing effective and purposeful training programmes for human resource development of such workers. The knowledge gaps need to be identified to increase the working competency of PEWs through training interventions for further improving livelihoods of their fellow farmers. A study was undertaken with structured interview schedule to assess the knowledge gaps of 54 PEWs in Mandi district of Himachal Pradesh. The study revealed that majority of PEWs belonged to middle age group, possessed formal education between matric to higher secondary, less farming experience, medium level of economic motivation and scientific orientation. Majority (68.52%) of PEWs possessed overall medium knowledge level about improved farm technologies and had adequate knowledge in regularly practiced farm practices. However, inadequate knowledge was observed in weed management, plant protection, protected cultivation, drip and sprinkler systems of irrigation technology. To achieve the potential for the uptake and successful implementation of extension programmes, regular capacity development of PEWs is henceforth suggested for improving their knowledge in these lacking areas for wider outreach of latest technologies. Pearson coefficient of correlation of PEWs age, farming experience and scientific orientation were found positively and significantly associated with overall knowledge level, whereas, educational qualifications and economic motivation showed positive but nonsignificant relationship.